Global Insights for National Reform: A Comparative Review of Education Management in Finland, Japan, Singapore, and the United States - Iswadi, Iswadi; Iriansyah, Herinto Sidik; Tamzil, Fachmi; Sari, Sarlina; Saridin, Rasman Bin (FKIP Universitas Lampung, 2025)
Global Insights for National Reform: A Comparative Review of Education Management in Finland, Japan, Singapore, and the United States. Objective: This study aims to analyze and compare the governance structures, curriculum models, teacher professionalism, learning strategies, assessment systems, and international achievements of education systems in Finland, Japan, Singapore, and the United States, and to derive strategic lessons relevant for improving the Indonesian education system. Methods: The research employs a qualitative comparative design based on a systematic literature review. The search strategy covered international databases (Scopus, Web of Science, ERIC, ProQuest, and Google Scholar) and official sources (OECD, UNESCO, and BPS). From 734 initial documents, 30 high-quality sources were selected through a screening process, eligibility assessment, and critical appraisal using CASP and MMAT tools. Data extraction followed a structured template and was analyzed through thematic coding and comparative synthesis across six key dimensions: governance, curriculum, teacher quality, learning strategies, student evaluation, and international achievement. Findings: The analysis shows that the success of education systems in developed countries is supported by key principles: Finland emphasizes trust-based governance and phenomenal learning, Japan prioritizes teacher collaboration through lesson study and discipline, Singapore utilizes meritocracy and structured career paths for teachers, and the United States emphasizes curriculum flexibility and local innovation. Indonesia, despite implementing the Independent Curriculum and the Freedom to Learn policy, still faces challenges related to resource inequality, teacher competency, and the implementation of innovative learning. Conclusion/Contribution: The study concludes that Indonesia must invest in teacher capacity, equitable distribution, and formative evaluation while adopting international best practices that align with its socio-cultural realities. The contribution of this study lies in providing evidence-based, contextualized policy recommendations that integrate global insights into Indonesia’s path toward a more equitable, innovative, and sustainable education system.Keywords: education system, education management, comparative studies, Indonesian education reform.